Bicrossed Products, Matched Pair Deformations and the Factorization Index for Lie Algebras - Agore, A.L.; Militaru, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
For a perfect Lie algebra h we classify all Lie algebras containing h as a subalgebra of codimension 1. The automorphism groups of such Lie algebras are fully determined as subgroups of the semidirect product h⋉(k∗×AutLie(h)). In the non-perfect case the classification of these Lie algebras is a difficult task. Let l(2n+1,k) be the Lie algebra with the bracket [Ei,G]=Ei, [G,Fi]=Fi, for all i=1,…,n. We explicitly describe all Lie algebras containing l(2n+1,k) as a subalgebra of codimension 1 by computing all possible bicrossed products k⋈l(2n+1,k). They are parameterized by a set of matrices Mn(k)⁴×k²ⁿ⁺² which are explicitly determined. Several matched pair deformations of l(2n+1,k) are described in order to compute the factorization index of some extensions of the type k⊂k⋈l(2n+1,k). We provide an example of such extension having an infinite factorization index.